Designing an industrially viable bimetallic catalyst for the polyol synthesis - Kadam, Jyoti R.; Khan, Tufeil Sartaj; Dhepe, Paresh L. (New Journal of Chemistry, 2023)
Designing new catalysts for the hydrogenation of sugars is important since the conventional catalyst RANEY (R) Ni faces issues such as leaching, operation under severe conditions (similar to 100 bar H-2) to achieve better yields and formation of complexes of Ni with polyols. To overcome these issues and to have an industrially acceptable methodology, bimetallic catalysts with varying metal loadings (Ru = 1.5 and 2 wt% and Co = 1.5, 3, and 4 wt%) were synthesized in the current work and their hydrogenation activities were evaluated for the synthesis of sugar alcohols from various sugars. It was revealed that the nature of the support plays an important role in deciding the selectivity and activity of the catalyst and amongst all the supports, basic alumina showed the best activity due to its contribution to the ring opening of sugars. C5 and C6 sugars were successfully hydrogenated to their respective sugar alcohols under low H-2 pressures (15 bar) and it was observed that as compared to the monometallic (1.5)Ru/Al-Basic catalyst, the bimetallic (1.5)Ru(3)Co/Al-Basic catalyst showed enhancement in the activity by almost 1.5 times. The improvement in the activity is suggested to be due to (i) observance of the synergistic effect between the base metal (Ru) and the promoter metal (Co); (ii) effect of basicity of the support; and (iii) electronic effect of Ru and Co. Recyclability of the catalysts and their efficiency to hydrogenate higher concentration substrate solutions (10-20 wt%) make the overall process industrially attractive.